Membrane vesicle production via cell-to-cell communication-induced autolysis in Streptococcus mutans - Ryo Nagasawa; Tamami Ito; Chika Yamamoto; Mio Unoki; Nozomu Obana; Nobuhiko Nomura; Masanori Toyofuku (Microbiology Spectrum, 2025)
ABSTRACT Membrane vesicles (MVs) released from bacteria into the extracellular environment play various roles in bacterial and bacterial–host interactions. In Gram-positive bacteria, cell wall degradation or damage is crucial for cytoplasmic MV (CMV) release because the cytoplasmic membrane must pass through the thick cell wall to the extracellular space. Although Streptococcus mutans, a major causative agent of dental caries, is known to release CMVs that are involved in pathogenicity and biofilm formation, the mechanism by which CMV production is triggered is unknown. In this study, we demonstrate that S. mutans induces CMV release via the Com system, a cell-to-cell communication system mediated by peptide signals. CMV release is primarily dependent on autolysin encoded by lytF, which is regulated by the Com system. Electron microscopy observations indicated that CMV release was accompanied by cell death in a subpopulation of cells. We compared the protein profiles of CMVs, showing that CMVs induced via the Com system contained not only secreted proteins but also cytoplasmic proteins specifically expressed during Com system activation. We further demonstrate that the functionality of CMVs in biofilm formation differed depending on how they were induced.IMPORTANCEBacteria release membrane vesicles (MVs) that are involved in diverse biological processes such as cell-to-cell communication and also affect the bacterial host through their immunomodulatory activity. Recent studies have focused on elucidating the mechanisms underlying MV formation. In Gram-positive bacteria, it has been shown that cell death represents a major pathway for MV formation. Since cell death would not benefit the dying cell, but may provide benefit to the remaining cells, it is essential to understand the regulatory mechanisms governing the formation of MVs at the population level. Here, we show that MV formation in Streptococcus mutans is regulated by cell-to-cell communication. A subpopulation of cells triggers cell death-meditated MV formation, from which the remaining cells derive benefits. This is the first report showing cell-to-cell communication regulates MV formation in Gram-positive bacteria that would provide insights into the regulatory mechanisms governing cell death-mediated MV formation at the population level.